NIAT PEMBELIAN KONSUMEN TERHADAP BUAH-BUAHAN SUBOPTIMAL DI SUPERMARKET KOTA BOGOR - Sarah Febrianti Sirait; Suprehatin; Joko Purwono (Jurnal Agribisnis Indonesia, 2025)
Consumer preference for quality fruit products, including perfect physical appearance attributes, has led supermarkets to set and sell fruit with certain quality standards, such as size, color, and ripeness. Currently, some supermarkets sell fruit with physical imperfections, known as suboptimal fruit, along with increasing attention to food waste, especially that resulting from the disposal of less-than-perfect products. This study aims to analyze the factors that influence consumer’s purchase intention on suboptimal fruit in supermarkets. This study uses primary data from 200 respondents who live close to six supermarkets in Bogor City that sell suboptimal fruit. Respondents were selected using voluntary sampling method. This study used the extended Theory of Planned Behavior (TPB) approach and the data were analyzed using structural equation modeling partial least square. The results showed that both TPB variables, namely attitudes, subjective norms and behavioral control and variables added to the model, namely environmental concerns, price discount promotions, and non-price promotions, had a significant effect on the purchase intention of suboptimal fruit in supermarkets. This research provides insight for supermarkets to increase purchase intention of suboptimal fruit through marketing strategies that focus on information, ease of access, product management and display arrangement, and consumer education.